Multiple regions dynamic stochastic general equilibrium model. (Journal of Economic Research & Business Administration, 2016)
In today's world there is interdependency between all economies. We have developed multiple regions dynamic stochastic general equilibrium model, which is the development of a model of two countries (Obstfeld & Rogoff, 2001) and its subsequent variants. In each country domestic and foreign goods are consumed. Price rigidity is modeled by applying the Calvo pricing. Model evaluation and analysis of the impact of internal and external shocks is carried out for the economy of Kazakhstan and its major trading partners.
Keywords: open economy; model of several countries; dynamic equilibrium; stochastic model; monetary policy; macroeconomic shocks.